Dysentery in Iquitos - Cornejo Donayre, Alberto (1960)
During the second quarter of 1960, in our laboratory in Lima, we examined 5 stool specimens from 5 different persons residing in Iquitos, who presented a dysenteric syndrome. The results are summarized in the following conclusions: 1.- The presence of E. histolytica has been confirmed in 5 stool specimens from 5 different people, all residents of Iquitos, demostrating the appearance of an endemic outbreak of amebiasis in that city. 2.- The wheatley technique was demostrated to be an effective staining method for amoebas in stool specimens fixed and preserved in P.V.A. solution; its use is recommended to standardize methods and obtain information on the incidence of amebiasis in Peru.